An Empirical Investigation of Self-Attitudes - Kuhn, Manford H.; McPartland, Thomas S. (American Sociological Review, 1954)
This chapter provides an initial demonstration of the advantages to empirical research from thus treating the self as attitudes. Although self has long been the central concept in the symbolic interaction approach to social psychology, little if anything has been done to employ it directly in empirical research. The self has been called an image, a conception, a concept, a feeling, an internalization, a self looking at oneself, and most commonly simply the self. There are two kinds of demonstration required to deal properly with the problem of the consistency of the test with its antecedent body of orientational theory. One is that of making explicit the chains of logic which went into the designing of the test, the test operations and the manipulations of the data obtained through its application. The other is that of showing that the test results correlate in some consistent patterns with the kinds of behavior which the orientation assets are related.